Reconfigurable surfaces employing linear-rotational and bistable-translational (LRBT) joints. (15th December 2020) - Li, Yang; Chandra, Anjini; Dorn, Charles J.; Lang, Robert J.
Abstract: Reconfigurable surfaces are useful in many applications. This paper proposes a type of reconfigurable surfaces that consist of rigid elements (tiles) connected by novel compliant joints. Depending on the actuation, these novel connecting joints can either operate as torsional hinges, which create isometric transformation (like origami folding) between connected tiles, or bistable translational springs, which accommodate metric-changing transformation between connected tiles. A specific example of a reconfigurable surface with square tile shape that can morph into flat, cylindrical (in two different directions), and spherical configurations with simple actuation is given.